2010
DOI: 10.1128/jvi.01495-10
|View full text |Cite
|
Sign up to set email alerts
|

Nodavirus-Induced Membrane Rearrangement in Replication Complex Assembly Requires Replicase Protein A, RNA Templates, and Polymerase Activity

Abstract: Positive-strand RNA [(؉)RNA] viruses invariably replicate their RNA genomes on modified intracellular membranes. In infected Drosophila cells, Flock House nodavirus (FHV) RNA replication complexes form on outer mitochondrial membranes inside ϳ50-nm, virus-induced spherular invaginations similar to RNA replication-linked spherules induced by many (؉)RNA viruses at various membranes. To better understand replication complex assembly, we studied the mechanisms of FHV spherule formation. FHV has two genomic RNAs; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 62 publications
7
71
1
Order By: Relevance
“…3A). As previously observed, under these conditions, in addition to the bands corresponding to RNA1 and RNA3, unspecific lower and higher comigrating bands are detected (45,51). In lsm1⌬ and pat1⌬ strains, an increase of 2-to 2.5-fold over the WT level was observed for RNA1 and RNA3 accumulation, while in the dhh1⌬ strain, RNA1 and RNA3 steady-state levels were not altered.…”
Section: Lsm1supporting
confidence: 57%
“…3A). As previously observed, under these conditions, in addition to the bands corresponding to RNA1 and RNA3, unspecific lower and higher comigrating bands are detected (45,51). In lsm1⌬ and pat1⌬ strains, an increase of 2-to 2.5-fold over the WT level was observed for RNA1 and RNA3 accumulation, while in the dhh1⌬ strain, RNA1 and RNA3 steady-state levels were not altered.…”
Section: Lsm1supporting
confidence: 57%
“…Similarly, BMV 1a protein induces replication complex-like spherules in which replication template RNA is recruited and sequestered, even in the absence of the 2a polymerase (47). In contrast, RNA polymerase activity is required for the formation of replication complex spherules by Flock House virus and Semliki Forest virus (50,51). In a certain host mutant, negative-strand RNA of tomato bushy stunt virus accumulates to levels similar to that in wild-type cells, but the negative-strand RNA is sensitive to nucleases, unlike in wild-type cells (52).…”
Section: Discussionmentioning
confidence: 99%
“…There is precedence for the involvement of the viral RNA in the RC maturation process. For example, it has been shown that the viral RNA along with the NSPs is necessary for formation of RCs in Semliki Forest virus-infected cells (38), and this is also the case for nodaviruses (16). In testing our hypothesis that CP chaperones P200, we examined the steps in P200 maturation that we had been studying in this and previous studies (29,30), finding no difference in processing efficiency, P150-P90 interaction, or membrane association by P200 or P150 in the presence or absence of CP.…”
Section: Discussionmentioning
confidence: 99%